Evaluation of Tensile Bond Strength of Metallic Prefabricated Posts Cemented with Different Luting Agents - Morgana Vicentin; Fernando Freitas Portella; Eduardo Galia Reston; Carlos Braga; André Luis Bianchi; Guilherme Anzilliero Arossi (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the tensile bond strength of prefabricated metal posts cemented with different luting agents. Material and Methods: Fifty single-rooted endodontically treated human teeth had their crowns cut, mounted into acrylic-resin blocks and then an 8mm depth post space were prepared. Prefabricated cylindrical metal posts were cemented using different luting agents: a zinc phosphate cement (SS White), a conventional glass ionomer cement (Vidrion C), two resin-modified glass ionomer cements (Vitremer and RelyX Luting 2) and a resin cement (RelyX ARC). Samples were stored in distilled water for seven days and then submitted to a tensile bond strength test until complete dislocation of the post. One-way analysis of variance and Tukey test for pairwise multiple comparisons were used to evaluate differences between luting agents. Results: Tensile bond strength was 563.88±203.41 N for zinc phosphate cement, 336.86 ± 137.64 N for Vidrion C, 515.24 ± 239.48 N for Vitremer, 828.47±433.99 N for RelyX Luting 2 and 1262.51 ± 356.29 for RelyX ARC. The Relyx ARC presented the highest tensile bond strength regard the luting agent tested (p< 0.05). Conclusion: RelyX ARC presented the higher tensile bond strength compared to the other luting agents evaluated.